Discurso científico, profesionalización histórica e identidad nacional mexicana / Scientific Discourse, Historical Profession, and the Mexican National Identity - López Meraz, Óscar Fernando; Villegas Loeza, Diana (Historiografías, 2017)
This article examines the relationship between scientific discourse and historical profession, on the one hand, and the Mexican identity, on the other, during the 19th and the 20th centuries. Its purpose is to prove that the bond between historiography and construction and strengthening of national identity has been operating until today and still persists. To explain this persistence, we take as a standpoint the hypothesis that the invention of a past was an essential requisite by the emergent Mexican state to help unit a population characterised by its differences and geographic distances, the situation brought about by the Mexican-American War (1846-1848) becoming a critical moment in this process.Key WordsScientific discourse, historical profession, nationalism, historiography, national identity.ResumenEl presente artículo examina las relaciones entre el discurso científico y profesionalización de la historia, de un lado, y la identidad mexicana, de otro, durante los siglos XIX y XX. El propósito del mismo es mostrar que ese vínculo entre la historiografía y la construcción y fortalecimiento de la identidad nacional todavía persiste en la actualidad. Para explicar dicho persistencia planteamos la hipótesis de que la invención de un pasado fue un requisito imprescindible para el Estado mexicano a la hora de buscar la cohesión de una población caracterizada por las diferencias y las distancias geográficas, siendo la coyuntura de la guerra con los Estados Unidos (1846-1848) un momento decisivo en este proceso.Palabras claveDiscurso científico, profesionalización de la historia, nacionalismo, historiografía, identidad nacional.